2019
DOI: 10.1161/circulationaha.119.041303
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Risk as a Function of Atrial Fibrillation Duration and CHA 2 DS 2 -VASc Score

Abstract: Background: Studies of patients with cardiovascular implantable electronic devices show a relationship between atrial fibrillation (AF) duration and stroke risk, although the interaction with CHA 2 DS 2 -VASc score is poorly defined. The objective of this study is to evaluate rates of stroke and systemic embolism (SSE) in patients with cardiovascular implantable electronic devices as a function of both CHA 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
159
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(163 citation statements)
references
References 27 publications
3
159
0
1
Order By: Relevance
“…In the KP-RHYTHM Study, a greater burden of AF identified using a noninvasive, 14-day continuous patch devices monitoring is associated with a higher risk of ischemic stroke and thromboembolism in adults with paroxysmal AF 35 . A recent study from Kaplan et al has shown that the duration of AF and CHA 2 DS 2 -VASc scores are both important components in assessing stroke risk and therefore in determining when OAC therapy should be initiated 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In the KP-RHYTHM Study, a greater burden of AF identified using a noninvasive, 14-day continuous patch devices monitoring is associated with a higher risk of ischemic stroke and thromboembolism in adults with paroxysmal AF 35 . A recent study from Kaplan et al has shown that the duration of AF and CHA 2 DS 2 -VASc scores are both important components in assessing stroke risk and therefore in determining when OAC therapy should be initiated 36 .…”
Section: Discussionmentioning
confidence: 99%
“…While improvement in symptoms is the major clinical endpoint of ablation for AF, AF duration and burden appear to correlate with risk of stroke 15,16,18,27 , raising the hypothesis that strategies that reduce AF burden could potentially mitigate stroke risk, even in the absence of completely eliminating recurrent AF. This hypothesis, along with the data that AF burden reduction may similarly reduce heart failure hospitalization and mortality was tested in a recent random-effect model meta-analysis of large databases, registries and a single randomized control trial (the CABANA trial 1 ) with a total of 241,372 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some authors have suggested that a reduction in AF burden may be a more objective endpoint rather than a binary outcome of recurrence as a measure of success 14 . This may be even more important given emerging data correlating AF duration and burden with risk of stroke 15,16,17,18 , a risk which may be attenuated in part by AF ablation 19 . The present exploratory analysis used a large de-identified electronic health record (EHR) dataset to assess how variations in defining AF recurrence and frequency and duration of monitoring influence an assessment of treatment success or failure.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the usefulness of risk scales [31,[36][37][38], the inclusion of new prognostic variables, their accessibility from primary care, their prognostic time, and their cost-effectiveness [6] in relation to the main objective should be considered: AF detection vs. prevention ictus. Our study did not use echocardiographic data [23,39] but shows specificities by gender.…”
Section: Interpretation Of the Study Resultsmentioning
confidence: 99%